Synthesis of a long chain alkylbiphenyl base stock and study on the lubricating properties. Issue 5 (5th August 2014) - Wang, Tinggui; Cai, Guoxing; Zhang, Letao; Ma, Li; Yu, Erlei; Eli, Wumanjiang
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The Friedel-Crafts alkylation of biphenyl with 1-octene was completed using methanesulfonic acid (MSA) as catalyst. Design/methodology/approach – Single factor experiments were carried out to investigate the influence of the molar ratio of biphenyl to 1-octene, the amount of MSA, reaction temperature and reaction time on the olefins conversion and the yield of product to obtain the optimal reaction conditions. Under the optimum conditions, a lubricating base stock was synthesized, and its physical, chemical and electrical properties were determined. Findings – The experimental results showed that after a 5 h reaction time at 353 K, the olefins conversion of 94.9 per cent and the yield of product of 69.3 per cent were obtained with a molar ratio of biphenyl to 1-octene of 1.2 and a molar ratio of MSA to 1-octene of 1. Under the optimum conditions, a lubricating base stock was synthesized, and its physical, chemical and electrical properties were determined. The results suggested that the synthetic base stock could be used as refrigeration oil. Originality/value – In this manuscript, biphenyl was alkylated with 1-octene using MSA as the catalyst and 2.6-di-t-butylphenol as polymerization inhibitor. Compared with traditional catalysts, it has so many advantages as low tendency to oxidize organic compounds, low toxicity and less corrosion. In addition, it can be readily separated from the reaction mixture and can be reused. Moreover, MSA is an environmentally friendly material.